Didactic materials: Mannequin for canine abdominal and vaginal palpation (Research, Society and Development, 2021)
Compared to the veterinary education system decades ago, ethical and welfare questions are of major relevance in the current scenario. Therefore, certain learning practices involving in vivo animal studies are no longer performed. To overcome this limitation, the use of mannequins has emerged as an interactive and immersive method of learning that simulates a real situation. The aim of this work is development mannequins for improve physiology of the reproductive apparatus of a bitch. Here, we used a plastic canine prototype to simulate the abdominal and vaginal palpation technique. An abdominal incision was made, filled with synthetic fiber, and a fictional uterus was placed. In the same mannequin, an orifice was created that correspond to the vagina. This model greatly helped in training students in performing palpation techniques, conducting the static evaluation, and assessing maternal-fetal ratio. Moreover, the physiology of the reproductive canine prototype made possible the demonstration of abdominal and vaginal palpation. This practice of vaginal palpation was found to be of great value since several students could easily take the examination and identify different stages of canine gestation, which could hardly be achieved using animals. Mannequins have received good student acceptance owing to their safety and ease to use, and resulted in a better understanding of the procedure to perform future in vivo animal studies.